2001
DOI: 10.1111/j.1752-0606.2001.tb01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Mars and Venus: Unequal Planets

Abstract: Self-help books, a pervasive and influential aspect of society, can have a beneficial or detrimental effect on the therapeutic process. This article describes a thematic analysis and feminist critique of the best-selling self-help book, Men are from Mars, Women are from Venus. This analysis revealed that the author's materials are inconsistent with significant family therapy research findings and key principles of feminist theories. His descriptions of each gender and his recommendations for improving relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…A recent survey demonstrated that Gray's (1992) original work and other popular relationship self-help books were among those used by 23% of couples in attempts to improve their relationships, and that among those who sought help, relationship books were the most frequent avenues for assistance (Doss et al 2009). From the perspective of therapists, Zimmerman et al (2001) described the difficult situation of talking with couples in therapy who had read one of Gray's books and "accepted Gray's messages" (p. 67), and thus needing to discuss with clients the awkward fact that the suggestions in the book generally are not consistent with relationship research.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…A recent survey demonstrated that Gray's (1992) original work and other popular relationship self-help books were among those used by 23% of couples in attempts to improve their relationships, and that among those who sought help, relationship books were the most frequent avenues for assistance (Doss et al 2009). From the perspective of therapists, Zimmerman et al (2001) described the difficult situation of talking with couples in therapy who had read one of Gray's books and "accepted Gray's messages" (p. 67), and thus needing to discuss with clients the awkward fact that the suggestions in the book generally are not consistent with relationship research.…”
Section: Introductionmentioning
confidence: 97%
“…Doss et al (2009) concluded that very little is known at all about the impact of relationship books on the individuals who use them. But many critics point to the importance of the stereotypical framework that such self-help books provide that then shape subsequent interpretations of ones partner's behaviors (e.g., Anderson 1998;Crawford 2004;Zimmerman et al 2001). One possible basis for understanding the books' effects can be drawn from social cognitive theories on the consequences of stereotypes.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations